Promoter and 11-kilobase upstream enhancer elements responsible for hepatoma cell-specific expression of the rat ornithine transcarbamylase gene. - Murakami, T (1990)
The gene for ornithine transcarbamylase (OTC; EC 2.1.3.3), a urea cycle enzyme, is expressed almost exclusively in the liver and small intestine. To identify DNA elements regulating transcription of the OTC gene in the liver, transient expression analysis was carried out by using hepatoma (HepG2) and nonhepatic (CHO) cell lines. The 1.3-kilobase 5'-flanking region of the rat OTC gene directed expression of the fused chloramphenicol acetyltransferase gene in HepG2 cells much more efficiently than in CHO cells. Analysis of deletion mutants of the 5'-flanking region in HepG2 cells revealed that there are at least one negative and two positive regulatory elements within the about 220-base-pair immediate 5'-flanking region. DNase I footprint analysis showed the presence of factors binding to these regulatory elements in nuclear extracts of rat liver and brain, and footprint profiles at the two positive elements exhibited liver-specific features. Transient expression analysis also revealed the existence of an enhancer region located 11 kilobases upstream of the transcription start site. The OTC enhancer was able to activate both its own and heterologous promoters in HepG2 but not in CHO cells. The enhancer was delimited to an about 230-base-pair region, and footprint analysis of this region revealed four protected areas. Footprint profiles at two of the four areas exhibited liver-specific features, and gel shift competition analysis showed that a factor(s) binding to the two liver-specific sites is related to C/EBP. These results suggest that both liver-specific promoter and enhancer elements regulate expression of the OTC gene through interaction with liver-specific factors binding to these elements.